Direct observation of the formation of a cyclic poly(alkyl sorbate) via chain‐growth polymerization by an N‐heterocyclic carbene initiator and ring‐closing without extreme dilution. Issue 20 (16th September 2020) - Muramatsu, Yuki; Takasu, Akinori; Higuchi, Masahiro; Hayashi, Mikihiro
Abstract: 1, 3‐Di‐ tert ‐butylimidazol‐2‐ylidene (NHC t Bu), which is one of the typical N ‐heterocyclic carbene (NHC), was found to initiate the anionic chain‐growth polymerization of methyl sorbate (MS) in toluene at −20°C. The polymerization was accelerated by an aluminum Lewis acid, that is, methylaluminum bis(2, 6‐di‐ tert ‐butyl‐4‐methylphenoxide) (MAD), to afford cyclic poly(MS)s. Subsequently, thiol‐ene click reactions of poly(MS)s with two different alkanethiols were performed using a photoradical initiator to obtain graft‐like polymers, which was for the microscopic observation of the chains directly by transmittance electron microscope (TEM). The contamination of linear polymers was hardly observed. This means that the polymers synthesized by our synthetic strategy were indeed cyclic polymers. We also compared the theoretical and experimental chain diameter and width for the graft‐like cyclic polymers, where these values were dependent on the molecular weight of the cyclic polymers regulated by the feed monomer/initiator ratio and length of the alkanethiols, respectively. Abstract : Thiol‐ene click reactions of cyclic poly(methyl sorbate)s with two different alkanethiols were performed using a photoradical initiator, and the resulting materials are examined using transmittance electron microscope (TEM). The contamination of linear polymers was hardly observed. This means the polymers synthesized by this synthetic strategy are indeed cyclic polymers ( JACS 2017, 139, 15005–15012). The theoretical and experimental chain diameter and width for the graft‐like cyclic polymers are also compared.